Evaluation and comparison of automated analysers on hepatic enzymes - Swetha, N.; Kavitha, A. (International Journal of Research in Medical Sciences, 2017)
Background:Clinical Biochemistry tests comprise over one third of all hospital laboratory investigation. The laboratory accreditation requirement has become an important aspect in selecting the analysers for analysing and evaluating the samples. Recently accrediting bodies are focusing on the importance of total quality management and assessment of trueness of laboratory measurements. The present study aimed to evaluate the hepatic enzymes using a single analytical methodology in 2 different automated analysers (semi autoanalyser and fully automated analyser) to understand the reliability of instrumentation on analytical methodology that would fit the laboratory performance standard. Methods:A total number of 50 serum samples from adult patients requested for liver function tests at Shri Sathya Sai medical college and research institute were analysed. The samples were evaluated for hepatic enzymes on (Cobasmira) Autoanalyser and (Biosystems) Semi Autoanalyser using the same analytical methodology and the values were compared between the 2 automated analysers. Data analysis was done by appropriate statistical methods. Results:No large differences were obtained in the values between the 2 automated analysers. Mean ± SD of each of the hepatic enzyme analysed by automated analysers were very close to each other indicating a minimum bias. Pearson’s correlation and scattered diagram showed significant positive correlation at 95% confidence interval between 2 automated analysers. Conclusion:The findings of this study confirm that both the automated analysers were reliable for evaluation of hepatic enzymes.